2018
DOI: 10.1371/journal.pone.0205698
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a novel continuous fetal Doppler (Moyo) improves quality of intrapartum fetal heart rate monitoring in a resource-limited tertiary hospital in Tanzania: An observational study

Abstract: BackgroundIntrapartum Fetal Heart Rate (FHR) monitoring is crucial for the early detection of abnormal FHR, facilitating timely obstetric interventions and thus the potential reduction of adverse perinatal outcomes. We explored midwifery practices of intrapartum FHR monitoring pre and post implementation of a novel continuous automatic Doppler device (the Moyo).MethodologyA pre/post observational study among low-risk pregnancies at a tertiary hospital was conducted from March to December 2016. In the pre-imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 26 publications
1
75
0
Order By: Relevance
“…15 In an observational study in Tanzania, cesarean rates were 5.4% for women with continuous Doppler monitoring, as compared with 2.6% for those with intermittent Pinard monitoring (P<0.001). 19 Other studies in Uganda 16 and Tanzania 17,18 showed no difference in cesarean rates between Doppler and Pinard groups.…”
Section: Findings On Clinical Management Associated With Abnormal Fhrmentioning
confidence: 93%
See 2 more Smart Citations
“…15 In an observational study in Tanzania, cesarean rates were 5.4% for women with continuous Doppler monitoring, as compared with 2.6% for those with intermittent Pinard monitoring (P<0.001). 19 Other studies in Uganda 16 and Tanzania 17,18 showed no difference in cesarean rates between Doppler and Pinard groups.…”
Section: Findings On Clinical Management Associated With Abnormal Fhrmentioning
confidence: 93%
“…Six studies addressed the effectiveness of Doppler versus Pinard stethoscope for the detection of abnormal FHR during intermittent or continuous FHR monitoring in the intrapartum period (Table 1). [15][16][17][18][19][20] Freeplay (wind-up) Doppler, 17 Moyo strap-on Doppler using the continuous or intermittent monitoring function, 18,19 and the Huntleigh pocket Doppler. 15…”
Section: Fhr Abnormalities and Adverse Perinatal Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study aimed to measure and identify challenges, rather than detect differences in outcomes for varying quality of care. Hence, it was still unable to determine the effect foetal monitoring has, if any, on birth outcomes [16]. The results should then lead to adequately-powered studies including clinical auditing in other LMICs to estimate the quality of the intrapartum (foetal) monitoring and linking it to birth outcomes.…”
Section: Strengths Limitations and Ethical Considerationmentioning
confidence: 99%
“…The gold standard for clinical quality assessment is direct observation that captures the real-life experiences and behaviour of birth attendants; yet, they are rarely used [10,11]. Similarly, few studies have assessed the adequacy of intrapartum foetal monitoring in low-resource settings [12][13][14][15][16]. This study used continuous direct observation to assess the quality of intrapartum care, with a specific focus on foetal monitoring and the structural requirements to delivering intrapartum quality care.…”
Section: Introductionmentioning
confidence: 99%